(untitled) (e-Journal of Linguistics, 2019)
Marriage system in the indigenous trust describes the relationship of supernatural effect on family kinship in the community. Such the relevance is the primary identifier and the identity of the diversity of the Indonesian nation. It is inevitable that a cultureas a pillar of diversity is a buffer for entering the era of multicultural and globalization. Values of Humanist is the power of social relation among individuals in the community groups. This paper describes the characteristic of marriage in society of Boti in East Nusa Tenggara who hold the original trust Halaika.The results shows behaviors that indicate homage to supernatural of Uis Pah (Ruler of the Earth), Uis Oe (Ruler of Water) and Uis Neno (Ruler of Heaven) in a series of marriages that is rich of value and meaning.